Analysis of Noncompliances with Legislative Requirements in Pharmacovigilance Materials of Registration Dossiers - E. O. Zhuravleva; N. Yu. Velts; G. V. Kutekhova (Безопасность и риск фармакотерапии, 2021)
Since 1 January 2021 the authorisation of medicines in the Russian Federation has to be performed according to the Eurasian Economic Union (EAEU) procedure. The Pharmacovigilance System Master File (PSMF) is the main document describing the pharmacovigilance system of the marketing authorisation holder (MAH) or its authorised representative.  The aim of the study was to analyse noncompliances with the EAEU requirements, which were revealed during PSMF assessment.Materials and methods: the authors analysed 687 pharmacovigilance documents included in registration dossiers that were submitted for assessment from 1 January to 30 June, 2021.  Results: the authors identified and systematised the main noncompliances with the EAEU requirements in terms of presentation, content, completeness of each PSMF section. They analysed the frequency of noncompliances in PSMFs and identified the most frequent flaws of MAHs’ pharmacovigilance systems.Conclusions: the authors give recommendations for elimination of significant noncompliances identified during PSMF assessment, which may include: timely updating, maintenance, and revision of the documents in accordance with changes in legislation and any other significant changes, regular training of pharmacovigilance staff, etc. The results of this review will be useful for MAHs as the main participants of the marketing authorisation process who are directly involved in the pharmacovigilance system management at the pre- and post-authorisation stages, and will help them prevent potential mistakes when drawing up pharmacovigilance system documents.